A Photonic Switch Based on a Hybrid Combination of Metallic Nanoholes and Phase-change Vanadium Dioxide - Sun, Miao; Taha, Mohammad; Walia, Sumeet; Bhaskaran, Madhu; Sriram, Sharath; Shieh, William; Unnithan, Ranjith Rajasekharan (Scientific reports, 2018)
A photonic switch is an integral part of optical telecommunication systems. A plasmonic bandpass filter integrated with materials exhibiting phase transition can be used as a thermally reconfigurable optical switch. This paper presents the design and demonstration of a broadband photonic switch based on an aluminium nanohole array on quartz utilising the semiconductor-to-metal phase transition of vanadium dioxide. The fabricated switch shows an operating range over 650 nm around the optical communication C, L, and U band with maximum 20%, 23% and 26% transmission difference in switching in the C band, L band, and U band, respectively. The extinction ratio is around 5 dB in the entire operation range. This architecture is a precursor for developing micron-size photonic switches and ultra-compact modulators for thin film photonics.